2005
DOI: 10.1007/s10750-004-4866-3
|View full text |Cite
|
Sign up to set email alerts
|

Water-level fluctuations in North American prairie wetlands

Abstract: Oscillatory water-level fluctuations are reversible changes in water levels around a long-term mean. Longterm water-level studies in wetlands in the prairie pothole region of North America and proxy data (e.g., tree rings) for water levels in this region indicate that oscillatory water-level fluctuations have occurred for thousands of years. Because there has been no standard set of terms to describe oscillatory water-level fluctuations, some terminology is proposed that is based on previous work on riverine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(37 citation statements)
references
References 73 publications
(84 reference statements)
0
37
0
Order By: Relevance
“…Of course, it could not be the only reason for vegetation change. However, there is no doubt that the hydrological regime with IEPs, including flood duration, frequency, and depth, could be the significant factor for vegetation change or succession, considering that most area of vegetation change are correlated with flood characteristics (IEPs) and numerous studies also support this observation (HowardWilliams 1975;Hughes 1990;Jean and Bouchard 1993;Gunderson 1994;Rea and Ganf 1994;Keddy 2000;Environment Canada 2002;Riis and Hawes 2002;Miller and Zedler 2003;Agostinho et al 2004;Van Der Valk 2005;Frieswyk and Zedler 2007;Maltchik et al 2007;Aroviita and HĂ€mĂ€lĂ€inen 2008;Wilcox and Nichols 2008;Todd et al 2010;Nam et al 2015).…”
Section: Results and Discussion: Hydrological Regime Using Ieps And Vmentioning
confidence: 99%
“…Of course, it could not be the only reason for vegetation change. However, there is no doubt that the hydrological regime with IEPs, including flood duration, frequency, and depth, could be the significant factor for vegetation change or succession, considering that most area of vegetation change are correlated with flood characteristics (IEPs) and numerous studies also support this observation (HowardWilliams 1975;Hughes 1990;Jean and Bouchard 1993;Gunderson 1994;Rea and Ganf 1994;Keddy 2000;Environment Canada 2002;Riis and Hawes 2002;Miller and Zedler 2003;Agostinho et al 2004;Van Der Valk 2005;Frieswyk and Zedler 2007;Maltchik et al 2007;Aroviita and HĂ€mĂ€lĂ€inen 2008;Wilcox and Nichols 2008;Todd et al 2010;Nam et al 2015).…”
Section: Results and Discussion: Hydrological Regime Using Ieps And Vmentioning
confidence: 99%
“…Previous studies have suggested that spatiotemporal climate variation and the corresponding drought/deluge cycles are common in the PPR, and they affect the dynamics of wetland water surface levels and the corresponding ecosystem services (Huang et al ., ). For example, field measured water levels and the number of pothole wetlands were reported to have good correlation with climate variables such as drought index and wet–dry cycles (e.g.Larson, ; Winter and Rosenberry, ; van der Valk, ; Withey and van Kooten, ). These well‐established relationships imply the sensitivity of prairie wetlands to climate change.…”
Section: Introductionmentioning
confidence: 97%
“…Cycles of fl ood and drought, (i.e., the temporal and spatial variation in water level) infl uence the availability of habitats with the conditions necessary for seedling establishment, thereby allowing the occurrence of species with diff erent life-strategies for the various phases of the hydrological cycle (Valk 2005). Changes caused by annual and recurrent fl ooding can result in plant adaptations that can increase species diversity; therefore, a high level of biodiversity adapted to diff erent conditions can be expected in fl oodplains (Alho & Sabino 2012;Pott & Silva 2015).…”
Section: Introductionmentioning
confidence: 99%